All systems red eaudiobook - Wells, Martha (The Murderbot Diaries, 2017)
All Systems Red is the first tense science fiction adventure novella in Martha Wells' series The Murderbot Diaries. For fans of Westworld and Ex Machina. All Systems Red by Martha Wells begins The Murderbot Diaries, a new science fiction action and adventure series that tackles questions of the ethics of sentient robotics. It appeals to fans of Westworld, Ex Machina, Ann Leckie's Imperial Raadch series, or Iain M. Banks' Culture novels. The main character is a deadly security droid that has bucked its restrictive programming and is balanced between contemplative self-discovery and an idle instinct to kill all humans. In a corporate-dominated spacefaring future, planetary missions must be approved and supplied by the Company. Exploratory teams are accompanied by Company-supplied security androids, for their own safety. But in a society where contracts are awarded to the lowest bidder, safety isn't a primary concern. On a distant planet, a team of scientists are conducting surface tests, shadowed by their Company-supplied 'droid - a self-aware SecUnit that has hacked its own governor module, and refers to itself (though never out loud) as "Murderbot." Scornful of humans, all it really wants is to be left alone long enough to figure out who it is. But when a neighboring mission goes dark, it's up to the scientists and their Murderbot to get to the truth.